Subarachnoid hemorrhage and extrapyramidal symptoms: a case report - Mammi, Patrizia; Brianti, Rodolfo; Galuppo, Laura; Caffarra, Paolo (Acta Biomedica Atenei Parmensis, 2016)
Introduction: Parkinsonism may occur after brain lesions such as subarachnoid hemorrhage (1), hydrocephalus (2,3), slit ventricle (4), or shunt revision (5).Until now, pathogenesis remains unclear. Method: Case Report. Results: We described the case of a 53 years Caucasian male with subarachnoid hemorrhage after anterior communicating artery aneurysm rupture, with subsequent complications and early development of bilateral extrapiramidal symptoms. A DatSCAN showed an impairment of the nigro-sytriatal dopaminergic way. Levodopa therapy induced complete symptoms remission. Conclusions: Patient developed Parkinson Disease responding to Levodopa. Subarachnoid hemorrhage itself, shunt placement and revision, hydrocephalus, slit ventricle: all of these complications occurred and could be possible causes of shear, torsion, and ischemia of the nigrostriatal projection fibres.